1999
DOI: 10.1046/j.1365-2885.1999.00191.x
|View full text |Cite
|
Sign up to set email alerts
|

Single‐dose pharmacokinetics of flumequine in halibut (Hippoglossus hippoglossus) and turbot (Scophthalmus maximus)

Abstract: Flumequine was administered to halibut (Hippoglossus hippoglossus) and turbot (Scophthalmus maximus) intravenously (i.v.) and orally (p.o.) at a dose of 10 mg/ kg bodyweight, and as a bath-treatment at a dose of 10 mg/L water for 2 h, using identical experimental designs. The study was performed in seawater with a salinity of 3% and a temperature of 10.3+/-0.4 degrees C (halibut) and 18.0+/-0.3 degrees C (turbot). Pharmacokinetic modelling of the data showed that flumequine had quite similar pharmacokinetic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 13 publications
2
19
0
Order By: Relevance
“…The reported 50.82% or 66.13% bioavailability of enrofl oxacin was much lower than that of quinolones in domestic animals (Hu and Feng, 1999;Zeng et al, 2003;Albarellos et al, 2005;Dimitrova et al, 2006). However, other quinolones in turbot were reported with lower bioavailabilities than the bioavailability of enrofl oxacin, such as a 27.90% bioavailability of oxolinic acid after 10 mg/kg at 16°C, and a 59% bioavailability of fl umequine after oral administration at 10 mg/kg at 18°C (Poher, 1998;Hansen and Horsberg, 1999).…”
Section: The Comparative Pharmacokinetics Of Enrofl Oxacinmentioning
confidence: 99%
“…The reported 50.82% or 66.13% bioavailability of enrofl oxacin was much lower than that of quinolones in domestic animals (Hu and Feng, 1999;Zeng et al, 2003;Albarellos et al, 2005;Dimitrova et al, 2006). However, other quinolones in turbot were reported with lower bioavailabilities than the bioavailability of enrofl oxacin, such as a 27.90% bioavailability of oxolinic acid after 10 mg/kg at 16°C, and a 59% bioavailability of fl umequine after oral administration at 10 mg/kg at 18°C (Poher, 1998;Hansen and Horsberg, 1999).…”
Section: The Comparative Pharmacokinetics Of Enrofl Oxacinmentioning
confidence: 99%
“…Atlantic halibut with a mean weight of 89 ± 15 g, held in seawater at 10.3°C were dosed with flumequine by intravenous injection and via oral administration in feed (10 mg kg -1 ) (Hansen & Horsberg 1999). Bioavailability following oral administration was 56% and plasma t 1/2 β values were 32 and 43 h respectively, following i.v.…”
Section: African Catfish Clarias Gariepinus and European Eel Anguillamentioning
confidence: 99%
“…group reached a C max of 1.4 µg ml -1 at a T max of 7 h. The distribution volume was 2.99 l kg -1 . Employing bath treatment for 2 h and a concentration of 10 mg l -1 of flumequine in the bath, the mean plasma concentration was calculated to be 0.08 µg ml -1 and bioavailability to be 5% (Hansen & Horsberg 1999). The authors concluded that a higher concentration of the drug in the bath and a prolonged treatment regime are needed to obtain therapeutic concentrations.…”
Section: African Catfish Clarias Gariepinus and European Eel Anguillamentioning
confidence: 99%
“…The quinolones flumequine and oxolinic acid have been used intensively to treat systemic bacterial infections like furunculosis, vibriosis and enteric redmouth disease in fish (Michel et al 1980; Austin et al 1983; Rodgers and Austin 1983; O'Grady et al 1988; Samuelsen 1997; Samuelsen et al 2000a). The widespread use of these drugs is mainly because of their relatively low minimum inhibitory concentrations (MIC) for the most susceptible fish pathogens (Martinsen 1993) and effective systemic distribution in fish (Chevalier et al 1981; Elema et al 1994; Martinsen and Horsberg 1995; Samuelsen and Ervik 1997; Hansen and Horsberg 1999, 2000; Samuelsen et al 2000b). The absorption and elimination of quinolones administered by bath in seawater has been previouly described for large (200 g) turbot, small (3–5 g) Atlantic halibut ( Hippoglossus hippoglossus L.), cod ( Gadus morhua L.), goldsinny wrasse ( Ctenolabrus rupestris L.) and corkwing wrasse ( Symphodus melops L.) (Samuelsen and Lunestad 1996; Hansen and Horsberg 1999, 2000; Samuelsen and Ervik 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The widespread use of these drugs is mainly because of their relatively low minimum inhibitory concentrations (MIC) for the most susceptible fish pathogens (Martinsen 1993) and effective systemic distribution in fish (Chevalier et al 1981; Elema et al 1994; Martinsen and Horsberg 1995; Samuelsen and Ervik 1997; Hansen and Horsberg 1999, 2000; Samuelsen et al 2000b). The absorption and elimination of quinolones administered by bath in seawater has been previouly described for large (200 g) turbot, small (3–5 g) Atlantic halibut ( Hippoglossus hippoglossus L.), cod ( Gadus morhua L.), goldsinny wrasse ( Ctenolabrus rupestris L.) and corkwing wrasse ( Symphodus melops L.) (Samuelsen and Lunestad 1996; Hansen and Horsberg 1999, 2000; Samuelsen and Ervik 2001). Using a concentration of 10 mg L −1 of flumequine in the bath and a 2‐h treatment, the plasma concentrations achieved in turbot were low (0.14 μ g ml −1 ) (Hansen and Horsberg 1999).…”
Section: Introductionmentioning
confidence: 99%